Is it safe to combine abdominoplasty and posterior vaginal repair in one surgical session? - Farroha Azzam; Hanna Hala (Indian Journal of Plastic Surgery)
Many multiparous women complain of protruded and pendulous abdomens and vaginal outlet relaxation which affect their sexual relationships with their male partners. This study included 47 patients who had these complaints. Some of these patients were working outside the homes and all were mothers of 2-5 children. Due of their home and job responsibilities, they did not have enough time or money for multiple surgeries in more than one session. Material and Methods: The age of these patients was 26-54 years and all patients had poor skin elasticity, pendulous excess subcutaneous fat and skin below the level of the anterior vulvar commissure, and a lax musculoaponeurotic anterior abdominal wall. Also, all patients had a relaxed vaginal outlet and 32 patients had rectocele. Careful perioperative assessment and management was done for each patient to ensure fitness for the long operation and to avoid complications. The combined surgical session consisted of two steps: abdominoplasty and posterior vaginal repair. All the patients were kept in the hospital for two days and they returned to their usual routines in the third week after surgery, and they resumed their sexual relationships with their male partners in the sixth week after surgery. Results: There were no serious complications and this approach was convenient for the patients and their families. The recovery time of the combined surgical session was the same as that of just abdominoplasty, and significantly less than the sum of the recovery periods if the two surgeries had been performed in two sessions. The cost of the combined surgical session was significantly less than doing the surgeries in two sessions. All the patients had significant improvement in their sexual relationships